Inductively coupled plasma-MS in drug development: bioanalytical aspects and applications. (August 2012) - van Heuveln, Fred; Meijering, Henri; Wieling, Jaap
The vast majority of today's modern bioanalytical methods for pharmacokinetic, pharmacodynamic and immunogenicity purposes are based on LC–MS/MS and immunoanalytical approaches. Indeed, these methodologies are suitable for a wide range of molecules from small to large. For a smaller but not insignificant group of compounds, LC–MS/MS is not suitable – or in some cases much less suitable – as a reliable bioanalytical methodology, and inductively coupled plasma (ICP)-MS is a more appropriate methodology. ICP-MS is one of these less widely used techniques in drug development. This methodology is predominantly used for elemental bioanalysis for pharmacokinetics, for imaging purposes, for mass-balance, food-effect and biomarker studies. In addition, in the last couple of years an increasing number of applications has been published, where ICP-MS and its various hyphenations (LC–ICP-MS, CE–ICP-MS) have been used for speciation/metabolism and proteomics studies. Here, the analytical potential, the quantitative bioanalytical aspects, the various modes of operation and the challenges of the application of ICP-MS in life sciences applications are given. This includes an overview of recent applications in this area in scientific literature, the various hyphenation possibilities and their application areas and the analysis of the various sample matrices applicable to these fields. It also provides a brief outlook of where the potential of this technique lies in the future of regulated bioanalysis and drug development.